1991
DOI: 10.1177/000348949110000604
|View full text |Cite
|
Sign up to set email alerts
|

Laser Uvulopalatoplasty in Treatment of Habitual Snoring

Abstract: Velopharyngeal sonorous snoring is best treated with uvulopalatopharyngoplasty (UPPP). To reduce surgical risks and minimize the morbidity, a simplified carbon dioxide laser uvulopalatoplasty (LUPP) was performed under local anesthesia. Among a total of 146 patients who had a LUPP performed, there was no significant bleeding or postoperative episodes of asphyxia. The procedure was well tolerated even by those patients with strong vomiting reflexes. The operation time was halved, as was the convalescence. Two p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0
5

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 14 publications
3
40
0
5
Order By: Relevance
“…Ryan and Love developed a study on 44 patients that underwent LAUP surgery and the polysomnographic results review an important decrease in AHI with an average of 27 percent 6 months postoperatively 27 . In literature we also found a series of side effects reported after this type of surgery -for example, Carenfelt reported that, from a total of 100 patients, 2 developed velopharyngeal insufficiency 28 .…”
Section: Olsen and Kernmentioning
confidence: 98%
“…Ryan and Love developed a study on 44 patients that underwent LAUP surgery and the polysomnographic results review an important decrease in AHI with an average of 27 percent 6 months postoperatively 27 . In literature we also found a series of side effects reported after this type of surgery -for example, Carenfelt reported that, from a total of 100 patients, 2 developed velopharyngeal insufficiency 28 .…”
Section: Olsen and Kernmentioning
confidence: 98%
“…Several procedures are available, each with advantages and disadvantages. The cure rates of laser uvulopalatoplasty (LAUP), cautery-assisted palatal stiffening surgery (CAPSO), and uvulopalatopharyngoplasty (UPPP) are 80-90% in patients with habitual snoring [3][4][5] . However, long-term results with these techniques Gomez Angel /Rodríguez-Diaz show a drop in the initial success rate [6] , and they have been associated with significant pain caused by extensive mucosal injury and in some patients may lead to velopharyngeal incompetence [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of laser techniques is that they are office procedures not requiring general anesthesia. Laser was probably used for the treatment of snoring for the first time in Sweden [4], but the currently most popular operation for snoring -laser-assisted uvuloplasty (LAUP) -was described by Kamami [5] a few years later. Other methods used for reduction of snoring include the submucous radiofrequency volumetric thermal reduction of the palate [6] , injections of a sclerosing agent to the palate [7] , and recently described soft palate implant procedures [8] .…”
Section: Introductionmentioning
confidence: 99%